Sleep quality of Chinese designers and the effects of digital screen time, stress, and job responsibility - Mao, Yongchun; Yang, Cunyuan; Raju, Gunasunderi (Intelektual Pustaka Media Utama, 2024)
The aim of this study was to describe the sleep status of Chinese designers and to identify the factors that affect their sleep quality. A total of 393 Chinese designers participated in the survey, which collected data on demographic information, digital screen time, stress, and the pittsburgh sleep quality index (PSQI). The average PSQI score of Chinese designers was 6.77, with 29% scoring equal to or higher than 9, indicating poor sleep quality. The most common sleep problem was difficulty falling asleep. Designers with management responsibilities had poorer sleep quality: the PSQI scores for those in design project management (M=8.74, SD=3.829) and design and management (M=9.05, SD=3.475) were significantly higher than for those in dedicated design (M=5.34, SD=2.908). There was a positive correlation between digital screen time for entertainment, work stress, other stress, and PSQI. The model equation was PSQI=1.160+0.276 * entertainment+0.675 * work stress+0.569 * other stress, with an r square of 0.232. Chinese designers should improve their sleep quality by reducing electronic entertainment and relieving stress. Managers in the design industry should pay special attention to their own sleep quality.